Safety of live attenuated herpes zoster vaccine in Australian adults 70–79 years of age: an observational study using active surveillance. Issue 3 (25th March 2021) - Phillips, Anastasia; Glover, Catherine; Leeb, Alan; Cashman, Patrick; Fathima, Parveen; Crawford, Nigel; Snelling, Thomas L; Durrheim, David; Macartney, Kristine
Abstract : Objectives: To assess the safety of live attenuated herpes zoster vaccine live (ZVL) through cumulative analysis of near real-time, participant-based active surveillance from Australia's AusVaxSafety system. Design and setting: ZVL was funded in Australia for adults aged 70 years from November 2016, with a time-limited catch up programme for those up to 79 years. This cohort study monitored safety in the first two programme years through active surveillance at 246 sentinel surveillance immunisation sites. Participants: Adults aged 70–79 years vaccinated with ZVL who responded to an opt-out survey sent via automated short message service (SMS) 3 days following vaccination (n=17 458) or contributed supplementary data through a separate, opt-in online survey at 16 and 24 days following vaccination (n=346). Primary and secondary outcome measures: Rates of overall and prespecified adverse events following immunisation (AEFI) by sex, concomitant vaccination and underlying medical condition. Signal detection methods (fast initial response cumulative summation and Bayesian updating analyses) were applied to reports of medical attendance. Results: The median age of participants was 72 years; 53% were female. The response rate following automated SMS was high (73% within 7 days of vaccination). Females were more likely than males to report any adverse event within 7 days of vaccination (RR 2.07, 95% CI 1.86 to 2.31); injection site reaction was the most commonly reported (2.3%, n=377). Concomitant vaccination was not associated with higher adverse event rates (RR 1.05, 95% CI 0.93 to 1.18). Rates of medical attendance were low (0.3%) with no safety signals identified. Supplementary opt-in survey data on later onset adverse events did not identify any difference in AEFI rates between those with and without underlying medical conditions. Conclusions: ZVL has a very good safety profile in the first week after vaccination in older adults. Active, participant-based surveillance in this primary care cohort is an effective method to monitor vaccine safety among older adults and will be used as a key component of COVID-19 vaccine safety surveillance in Australia.